2022
DOI: 10.1200/jco.2022.40.16_suppl.1044
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of HER2Neu-low in metastatic breast cancer.

Abstract: 1044 Background: HER2-Low (or HER2-equivocal, FISH negative) breast cancer has historically been treated as HER2-negative; however, recent evidence suggests that there may be prognostic and/or predictive differences between the two. We explore demographic characteristics and clinical outcomes of HER2-negative and HER2-low metastatic breast cancer (MBC) patients using real world data. Methods: We queried the National Cancer Database to identify MBC patients that were HER2 0, HER2 1+, or HER2 2+ per immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We evaluated 15 studies 4,10,1214,16,18,19,22,24,2528 ; 7 new studies 10,13,14,16,19,24,27 were included and 6 studies 3,15,20,23,29,30 were excluded from evaluation of the OS of the overall population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated 15 studies 4,10,1214,16,18,19,22,24,2528 ; 7 new studies 10,13,14,16,19,24,27 were included and 6 studies 3,15,20,23,29,30 were excluded from evaluation of the OS of the overall population.…”
Section: Resultsmentioning
confidence: 99%
“…In all, 14 studies 3,4,12,15,18,20,22,23,25,26,[28][29][30]32 (n = 81,486) were included to evaluate the OS of the overall population. The results demonstrated that patients with HER2-low BC had better OS than those with HER2-zero BC (HR = 0.90; 95% CI: 0.85-0.97; p = 0.003), despite considerable heterogeneity between the studies (p < 0.01; I 2 = 93%) (Figure 2(a); Table 2).…”
Section: Comparison Of Os Between Patients With Her2-low and Her2-zer...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the strong interest, the data on the association between HER2-low status and CDK 4/6 inhibitor efficacy are still controversial. A similar problem was present with the survival outcomes with early HER2-low breast cancer, with studies with contrasting results also available [ 39 42 ]. One of the main reasons regarding this issue could be the problems and variability with HER2-low case definition.…”
Section: Discussionmentioning
confidence: 84%
“…After duplicate removal and exclusion of non-relevant records, 42 studies were included in the present meta-analysis (Figure 1). Among them, 12 studies included data from patients affected by metastatic breast cancer, [15][16][17][18][19][20][21][22][23][24][25][26] 27 analysed data from patients with early breast cancer and 3 studies analysed subjects in both settings. [54][55][56] A total of 1 797 175 patients were eligible for this analysis, of whom 1 697 079 had early disease (1 118 389 HER2-low and 578 690 HER2-zero) and 100 096 had advanced disease (59 798 HER2-low and 40 298 HER2-zero).…”
Section: Resultsmentioning
confidence: 99%